Metabolic syndrome and psoriasis: a study in 97 patients - Ferdinando,Lana Bassi (2018)
SUMMARY BACKGROUND: Psoriasis is associated with higher prevalence of metabolic syndrome (MS). The prevalence of MS varies according to the studied population as it suffers influence of genetics, aging, sedentary behaviour and diet. OBJECTIVE: To study the prevalence of MS in local psoriasis patients and the influence of psoriasis variables on its appearance. METHODS: A group of 97 psoriasis patients were studied for MS and compared with 97 controls. Psoriasis type, nail involvement, psoriasis extension measured by PASI (Psoriasis Area and Severity Index) were obtained through physical examination and history of previous myocardial infarction, angina and stroke were obtained through chart review. RESULTS: Comparison of MS prevalence in psoriasis patients (49.4%) with controls (35.0%) showed difference with p=0.04; OR=1.8 (95%CI=1.02-3.23). Patients with psoriasis had higher body mass index (p=0.02), higher systolic blood pressure (p=0.007), lower HDL cholesterol (p=0.01), higher glucose (p=0.04), higher waist circumference (p=0.003) and more angina pectoris (p=0.03;OR=2.5; 95% 0=1.04-6.15) than controls. When psoriasis sample with and without MS were compared, those with MS were older (p=0.0004), had disease onset at older age (p=0.02), more tobacco exposure (p=0.02), and a tendency to have less scalp involvement (p=0.06) in univariate analysis. Logistic regression showed that only age and scalp involvement were independently associated with MS in the psoriasis sample. CONCLUSION: In our psoriasis sample, MS prevalence is high and the items that deserve more attention are central obesity, low HDL, hypertension and smoking habits. In the psoriasis group, MS was associated independently with older age and less scalp involvement.